Conflicted Science. Issue 1 (January 2015) - Rowe, Sylvia; Alexander, Nick
<x xml:space="preserve">Abstract</x> Much has been written in the peer-reviewed literature about conflicts of interest in scientific research, including food research. Some authorities have called for more stringent management of such conflicts. Some have pointed out the relationship between financial conflicts of interest and other kinds of biases that may affect the direction or interpretation of research. Relatively little if anything has appeared in the literature about the possible biases of those who report or comment on nutrition and other health research. In this article, such "communication bias" is explored in some depth, and strategies are discussed for disclosing and managing the philosophical, emotional, value-based, or other biases that influence the interpretation of nutrition and health science. At a minimum, the authors argue for greater awareness and disclosure of such influences on the reporting of diet and health information.